2016
DOI: 10.1186/s12877-016-0315-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of combined physical and cognitive training on cognition: a systematic review

Abstract: BackgroundNumerous daily activities require simultaneous application of motor and cognitive skills (dual-tasking). The execution of such tasks is especially difficult for the elderly and for people with (neuro-) degenerative disorders. Training of physical and cognitive abilities helps prevent or slow down the age-related decline of cognition. The aim of this review is to summarise and assess the role of combined physical-and-cognitive-training characteristics in improving cognitive performance and to propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
217
3
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(237 citation statements)
references
References 77 publications
11
217
3
6
Order By: Relevance
“…Behavioural strategies such as those leading to "texting lanes" in other countries may be a useful tool to address this issue more broadly [26]. Targeted approaches could include specific training to improve dual-tasking in both younger and older people [27,28], with evidence that combined physical and cognitive training can lead to cognitive improvement in attention and executive function [29]. While neurodegeneration is not the only factor contributing to the slowing of gait speed, practice in texting while walking therefore has the potential to maintain the complex pathways at the cognitive-motor interface.…”
Section: Resultsmentioning
confidence: 99%
“…Behavioural strategies such as those leading to "texting lanes" in other countries may be a useful tool to address this issue more broadly [26]. Targeted approaches could include specific training to improve dual-tasking in both younger and older people [27,28], with evidence that combined physical and cognitive training can lead to cognitive improvement in attention and executive function [29]. While neurodegeneration is not the only factor contributing to the slowing of gait speed, practice in texting while walking therefore has the potential to maintain the complex pathways at the cognitive-motor interface.…”
Section: Resultsmentioning
confidence: 99%
“…Coordination training combining balance, limb coordination, spatial orientation and reaction time tasks are also effective in modulating brain structure and function that are associated with improvements in cognition and motor performance (Voelcker-Rehage et al, 2010, 2011). Comparative studies revealed that combining motor and cognitive demands during exercising can even lead to greater enhancements in cognition than training the domains separately (Fabre et al, 2002; Oswald et al, 2006; Lauenroth et al, 2016). It has been argued that enhanced neuronal metabolic processes induced by physical activity can only be exploited efficiently when the brain is simultaneously challenged by cognitive demands (Oswald et al, 2006; Bamidis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Iako fizičko vežbanje nesumnjivo doprinosi unapređenju kognitivnog funkcionisanja čoveka ne treba ga shvatati kao "vakcinu" protiv neurodegenerativnih bolesti. Fizičko vežbanje svakako predstavlja jedan od važnih protektivnih faktora, ali samostalno ne može zameniti aktivnosti koje direktno razvijaju i unapređuju kognitivno funkcionisanje (Duay & Bryan, 2006;Henderson, 2014;Lauenroth, Ioannidis, & Teichmann, 2016). Stoga, u kombinaciji sa "mentalnim treninzima", fizičku aktivnost treba shvatati kao pomoć u unapređenju kognitivnih funkcija i, svakako, kao jednu od osnova opšteg psihofizičkog zdravlja.…”
Section: Zaključakunclassified